2011
DOI: 10.1007/s10532-011-9503-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the efficacy of Aspergillus sp. EL-2 in textile waste water treatment

Abstract: Fungal biomass has the ability to decolorize a wide variety of dyes successfully through a number of mechanisms. A brown rot isolate, previously identified as Aspergillus sp. EL-2, was used in the aerobic treatment of textile waste water efficiently. In the current work, the treated waste water was tested chemically using more than one combined treatment. Microbial toxicity, phytotoxicity, genotoxicity and cytotoxicity were also studied to assess the toxicity level for each treatment. The obtained data suggest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…MFCs inoculated with gamma-irradiated pre-treated cells did not only show the highest MFC performance, but it also exhibited high decolorization and low toxicity values for the treated wastewater. Enhancing decolorization of real textile wastewater was reported to decrease toxicity (Gomaa, Abdel El Kareem, & Fathey, 2011). Therefore, we can claim that gamma radiation affects bacterial cell permeability as well as induces EPS production as stress response, contributing to release of electrons and/or other metabolites, while EPS acted as the transient media for electron transfer, in addition to the overall increase in cell adhesion to the anodic surface.…”
Section: Discussionmentioning
confidence: 99%
“…MFCs inoculated with gamma-irradiated pre-treated cells did not only show the highest MFC performance, but it also exhibited high decolorization and low toxicity values for the treated wastewater. Enhancing decolorization of real textile wastewater was reported to decrease toxicity (Gomaa, Abdel El Kareem, & Fathey, 2011). Therefore, we can claim that gamma radiation affects bacterial cell permeability as well as induces EPS production as stress response, contributing to release of electrons and/or other metabolites, while EPS acted as the transient media for electron transfer, in addition to the overall increase in cell adhesion to the anodic surface.…”
Section: Discussionmentioning
confidence: 99%
“…Example, the research made by Kamaruddin reported that biological treatment such as aerobic and anaerobic were disabled to degrade the azo dyes [4]. This is due to the incomplete destruction of the organic compounds during treatment process that caused the azo dyes being transfer onto biomass [4,13,14]. In addition, advanced oxidation processes (AOPs) like IOP Publishing doi:10.1088/1755-1315/1216/1/012037 2 ozonation, UV-Fenton, and photochemical required continuous chemical supplies (Fenton's reagents) during treatment.…”
Section: Introductionmentioning
confidence: 99%
“… 7 Its effect may lead to cytotoxicity and genotoxicity and treating the effluent efficiently can help alleviate this toxicity. 8 The hazardous effect of wastewater re-uses lies in the pathway of their release. Industrial wastewater is collected with household and agriculture drainage water, mixed and then treated for re-use in irrigation.…”
Section: Introductionmentioning
confidence: 99%